Ultra Performance Liquid Chromatography Determination of Pravastatin Sodium in Erythrocytes - Abdel-Hamid, M.; Ibrahim, M.F.; Harisa, G.I.; Alanazi, F.K. (Asian Journal of Chemistry, 2011)
This work comprised a novel, rapid, accurate, precise and specific ultra performance liquid chromatography method for pravastatin determination in erythrocytes. Pravastatin sodium was extracted from pravastatin loaded erythrocytes by liquid/ liquid extraction. The method was performed on acquity® UPLC system, acquity® UPLC BEH C18 column (2.1 mm × 50 mm, 1.7 μm). The mobile phase was a mixture of 0.25 % formic acid in distilled water and acetonitrile (65:35, v/v), with flow rate of 0.5 mL/min and injection volume was 1 μL. Photodiode array (PDA) detector was set to acquire 3D data from 210 to 280 nm while the 2D channel was recording at 237 nm, the column temperature was kept at 50 ºC while sample temperature was kept ambient. Method was validated and found to be linear, selective, precise and accurate as per FDA guidelines with low limit of detection 0.1 μg/mL and low limit of quantitation 0.5 μg/ mL.